Pengembangan Media Pembelajaran PowerPoint Interaktif Hidangan Asia Tenggara - Putri, Ni Luh Ari Melani; Ekayani, Ida Ayu Putu Hemy; Sukerti, Ni Wayan (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to 1) to describe the steps in developing interactive PowerPoint media on Southeast Asian cuisine using the 4D model, 2) to determine the feasibility of interactive PowerPoint learning media on Southeast Asian cuisine, and 3) to determine student responses to interactive PowerPoint learning media on Southeast Asian cuisine in the Culinary Arts Vocational Education study programme.. This research is a research and development study, using the 4D model which consists of four stages, namely Define, Design, Develop, and Disseminate. This research involved subject matter experts, media and learning design experts, and students who had passed the Southeast Asian cuisine course as respondents. Data collection was conducted through a Likert scale questionnaire distributed to experts and students. The data was analysed descriptively and quantitatively by calculating the percentage of assessments from experts and student responses. Based on the results of the test by media and learning design experts, the feasibility percentage was 96.4%, while the subject matter experts' test resulted in a feasibility percentage of 98%. Thus, the media was declared ‘Highly Feasible’ for use as learning media. The results of the student response test showed that the PowerPoint media received a positive response. Based on the collected data, the learning media obtained a suitability percentage of 89.5%. From these findings, it can be concluded that the Interactive PowerPoint on Southeast Asian Cuisine is ‘Highly Suitable’ for use as learning media in the Asian Cuisine course.